PRO-KONTRA PEREMPUAN DAN POLITIK DALAM PERSPEKTIF FEMINISME MUSLIM - Sastrawaty, Nila (JURNAL SIPAKALEBBI, 2023)
This paper aims to examine the views of Qasim Amin, Aminah Wadud Muhsin, Fatimah Mernissi, and Asghar Ali Engineer regarding the factors that influence the pros and cons of political women leadership. This study uses a qualitative method whose data comes from library research. The results of this study indicate that Muslim feminists are based on the interpretation of the Koran and Hadith to obtain a comprehensive picture of the principle of Islamic equality.Indonesia, as a country where the majority of the population is Muslim, it is undeniable that Muslim feminist thought has contributed to the dynamics of thinking about the role of women in politics, as well as the challenges faced to date, namely; interpretation of religious texts, patriarchal culture, and access to education for women.